PENGARUH KUALITAS PELAYANAN TERHADAP PEMBELIAN ULANG DAN PROMOSI SEBAGAI MODERASI - Toman Ezra; Sunaryo, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study is to analyze the effects of service quality on the repeat purchase made by the customers of Superindo branch of Tlogomas in Malang city with promotion as the moderator. This research is categorized as explanatory research as it observes the quality of variables that explain certain phenomena, as well as explain or prove the relationships or influences between variables. Using non-probability sampling method and purposive sampling technique, a number of 160 people were selected as the respondents. The population in this study are consumers of Superindo Tlogomas Branch who have made purchases at least 2 times. The location of this research is Superindo Tlogomas Branch which is located on Jl. Raya Tlogomas No. 5a District Lowokwaru. The data was analyzed using multiple linear regression in SPSS 20. This study finds that service quality has positive and significant effects on repeat purchase, that service quality and promotion positively affect repeat purchase, and that promotion fully moderates the relationship between service quality and repeat purchase.